2016
DOI: 10.1016/j.apenergy.2016.04.049
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of automated measurement and verification (M&V) techniques for energy savings in commercial buildings

Abstract: Trustworthy savings calculations are critical to convincing investors in energy efficiency projects of the benefit and cost-effectiveness of such investments and their ability to replace or defer supply-side capital investments. However, today's methods for measurement and verification (M&V) of energy savings constitute a significant portion of the total costs of efficiency projects. They also require time-consuming manual data acquisition and often do not deliver results until years after the program period h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 18 publications
0
68
0
2
Order By: Relevance
“…For most Measurement & Verification activities, 12 months of pre (i.e., 'baseline') and post (i.e., 'intervention') data is the recommended amount of data, though recent research has shown that the results from 6 months of data yield similar results in most cases [24]. The concern always arises that something substantial may have changed in the building which is unrelated to the intervention that the analyst wishes to evaluate, and then confounds the results.…”
Section: Randomized Controlled Trialmentioning
confidence: 90%
“…For most Measurement & Verification activities, 12 months of pre (i.e., 'baseline') and post (i.e., 'intervention') data is the recommended amount of data, though recent research has shown that the results from 6 months of data yield similar results in most cases [24]. The concern always arises that something substantial may have changed in the building which is unrelated to the intervention that the analyst wishes to evaluate, and then confounds the results.…”
Section: Randomized Controlled Trialmentioning
confidence: 90%
“…4. The forecasting accuracy of other machine learning (ML) methods can be higher than regression in some cases [31,32], although regression-based approaches such as time-of-week-and-temperature [33] still perform very well [32,34] and may be preferred for simplicity. Note that this is a limitation of regression, not the overall Bayesian paradigm, although regression is the way most M&V analysts would use Bayesian methods.…”
Section: Caveatsmentioning
confidence: 99%
“…The Coefficient of Variation on the Root Mean Square Error (CV(RMSE)) and Normalised Mean Bias Error (NMBE) have been found to be the most popular criteria against which Calibrated Simulation M&V model prediction goodness of fit is evaluated [68]. The NMBE measures whether the model consistently overpredicts or underpredicts energy use.…”
Section: Application To Meter Calibrationmentioning
confidence: 99%